The musical side of Robert Gabriel Mugabe - Muranda, Richard; Maguraushe, Wonder; Chimbudzi, Weston (Leaders for Africa Network, 2022)
Chapter 6, discuss the support for and taste of music drawing from various events and incidences – direct and indirect – about his life. The chapter examines and discusses Mugabe’s views regards musicals at graduation ceremonies at selected state universities in Zimbabwe – for which he presided over as Chancellor. By focusing on Mugabe’s close interaction with the Zimbabwe Republic Police (ZRP) Police Band, as well as his observed deployment of liberation war songs as part of his tactics for the sustenance of his political hegemony,his apparent love for classical and folk music, Muranda, Maguraushe and Chimbudzi make submissions that, there was a softer side to Mugabe, after all. The chapter also recognises and commends Mugabe for his support for the academic study of music in higher education institutions, which has seen the contemporary teaching and learning of music up to degree levels. Avery pertinent contribution that the chapter makes is its recognition of how Mugabe used music as a medium of political communication to reinforce and sustain his political hegemony and philosophies (even in the face of the threats of intraparty factional wars that threaten it) as well as to legitimate his nearly four decades of rule